Anal canal squamous cell cancer: surgıcal therapy, when? - Selcuk Kaya; Onder Altın; Yunus Emre Altuntas; Gokhan Yaprak; Hasan Fehmı Kucuk (Medicinski glasnik, 2019)
Aim: To describe a therapeutic approach, indications for abdominoperineal resection (APR), survival and oncological results for patients who received treatment in our surgical clinic for anal canal squamous cell cancer (SCC). Methods: Patients were randomized into two groups according to the treatment method: Group 1-Chemoradiotherapy (CRT) without surgery, Group 2-CRT + APR. Results: Eighteen patients with anal canal SCC were included in the study; 11 (61.1%) patients were in Group 1 and 7 (38.8%) in Group 2. Reasons for APR was as follows: three patients had insufficient CRT, two had recurrence after CRT, one had complete faecal incontinence and one patient had rectovaginal fistula. Overall five year survival (OS) and disease free survival (DFS) was 77.7% and 72.7%, respectively. Comparing two groups five year OS was 90.9% and 57.1%, whereas DFS was 81.8%, 57.1%, respectively (p=0.389 and 0.324, respectively). Conclusion: Gold standard therapy for anal canal SCC is CRT. However, APR should be applied as an escape treatment for patients suffering from tumour progression, insufficient CRT and recurrence (30%).
Keywords: abdominoperineal resection; local excision; Nigro protocol